1978
DOI: 10.1021/bi00606a009
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate transport in yeast mitochondria: purification and characterization of a mitoribosomal synthesis dependent proteolipid showing a high affinity for phosphate

Abstract: It is possible to obtain from yeast mitochondria a proteolipid able to bind phosphate, by two different procedures. One of them, generally used for lipid extraction, leads to the preparation of a more active crude proteolipid. This crude proteolipid has been purified by various chromatographic procedures and the active fraction, in phosphate binding, is always associated with cardiolipin. Its molecular weight seems to be close to 10000. The phosphate binding shows ligand saturation behavior and is inhibited by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0

Year Published

1981
1981
1990
1990

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 24 publications
1
20
0
Order By: Relevance
“…For example, carrier proteins for phosphate, chloride, and sulfate transport have been recently identified and isolated from bacteria (1,20), fungi (6), and human red blood cells (see reviews 10,24). In the red blood cell studies (2-4, 8, 11, 17), several nonpermanent, amino-reactive reagents (e.g., SITS,2 DIDS, DADS, and NAP-taurine), which covalently bind to the plasmalemma, have been used to identify and characterize the band 3 membrane protein as the carrier for CF-and s042-transport.…”
mentioning
confidence: 99%
“…For example, carrier proteins for phosphate, chloride, and sulfate transport have been recently identified and isolated from bacteria (1,20), fungi (6), and human red blood cells (see reviews 10,24). In the red blood cell studies (2-4, 8, 11, 17), several nonpermanent, amino-reactive reagents (e.g., SITS,2 DIDS, DADS, and NAP-taurine), which covalently bind to the plasmalemma, have been used to identify and characterize the band 3 membrane protein as the carrier for CF-and s042-transport.…”
mentioning
confidence: 99%
“…In [28,29] it was suggested that one proteolipid could be the Pi binding proteolipid. The possibility that the 10 000 M r band was the Pi-binding proteolipid [ 12,13 ] is under investigation.…”
Section: Resultsmentioning
confidence: 99%
“…From initial observations [11 ] a proteolipid having affinity for Pi was extracted from yeast mitochondria by organic solvents [12]. This proteolipid is mitochondrially translated and its participation in phosphate transport has been suggested [12,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations